Cone-Beam Computed Tomography: Time for an Evidence-Based Approach. Issue 1 (March 2013) - Horner, Keith
Cone-beam computed tomography (CBCT) is an imaging technology that has revolutionised dental imaging in the last decade. Although of particular value to specialists performing implant treatment, it is increasingly being adopted by general dental practitioners. As the radiation dose is higher than that of conventional radiography, it is important to consider its diagnostic efficacy for the common tasks performed in general dental practice, such as caries diagnosis, endodontics and the detection of periapical pathosis. Any new imaging technique needs to have proven advantages over existing techniques before it is adopted, yet the evidence remains quite limited. Furthermore, image quality and radiation doses vary enormously between different manufacturers' equipment, so that extrapolating results of one piece of research from one CBCT machine to another is fraught with pitfalls. Radiation doses with CBCT are typically an order of magnitude higher than conventional radiography. There is scope, however, for reducing these doses by judicious adjustment of exposure factors and limiting the field of view to the smallest dimensions consistent with the clinical situation. There is still a long way to go before we understand the value of CBCT in dentistry. High quality research evidence is needed, particularly with regard to assessing whether using CBCT improves patient outcomes.